THE USE OF INTERACTIVE MULTIMEDIA (MACROMEDIA FLASH) TO INCREASE CREATIVE THINKING ABILITY OF STUDENTS IN BASIC PHYSICS SUBJECT - Marnita, M.; Ernawati, E. (Jurnal Pendidikan Fisika Indonesia, 2017)
Students were intellectuals who should have the ability to think critically, one of which is the creative thinking skills. However, the students' limited ability in basic physics as well as the limitations of using a variety of multimedia resulted in basic physics final exam results lower than 6 on average from maximum value of 10. This leads to the lower creative thinking skills of students in basic physics. This research is a Quasi Experiment research on students in the first semester of academic year 2014/2015 which amounted to 38 people. This research is expected to increase creative thinking skills as well as lecturers and students activities. Data obtained from this study is the data of creative thinking skills of students and data on the observation of activity of lecturers and students. The data were analysed by using formula percentage of completeness of learning outcomes, gain indexes and statistical t-test. Based on the results of data analysis it is showed that the use of interactive multimedia (Macromedia Flash) can improve creative thinking skills of students.